Program Pendidikan Non Formal Berupa Pelatihan Produksi dan Pemasaran VCO Di Desa Lintas Utara Kecamatan Keritang Kabupaten Indragiri Hilir Riau - Fangestu, Indra Wahyuni Firli; Ridwan, Muannif (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
This non-formal education program in the form of VCO production and marketing training in the village of Lintas Utara, Keritang sub-district, Indragiri Hilir Regency, Riau Island is a community service activity carried out by students and lecturers in a series of KKN (Community Service Program) activities. This type of research is a qualitative research that produces description in the form of written or spoken words of people and observable behavior. This study concludes that the existence of non-formal education in the form of training VCO production and marketing in Lintas Utara village has not received special attention from the local village government and community. This can be seen from the lack of village government initiatives and the absence of non-formal educational institutions related to increasing knowledge and skills to help improve the economy of the community whose livelihoods are mostly local/ordinary oil palm and coconut farmers.